Drawing a Roadmap for Oil Pricing Reform - Kojima, Masami (World Bank, Washington, DC, 2013)
In 2011, the median oil imports rose to 5 percent of gross domestic product for net importers. In the past several years, many governments have not passed through the world oil price increases to consumers fully. As a sign of divergent pricing policies, the retail prices of gasoline, diesel, and cooking gas in January 2013 varied by a factor of 190, 250, and 70, respectively, across developing countries. Policies to keep oil product prices low to benefit the economy and protect the poor have had a number of unintended negative consequences, including flourishing corruption in the oil sector and entrenchment of monopoly operators or inefficient firms through which subsidies are channeled, stifling competition and raising costs. The path to market-based pricing depends on the starting conditions: the gap between current and market-based price levels, the level of public awareness about the extent of departure from market prices, the degree of market concentration and competition in downstream oil, the subsidy delivery mechanism where subsidies are provided, the robustness of social service delivery, and the perceived credibility of the government. The evidence presented in this paper suggests that pricing reform often does not have a clear end and should instead be viewed as a continuous process of adjustment and search for mechanisms that take into account the country's institutions and political system, and the oil sector's market structure, infrastructure, and history.